Single phase induction motor control using pwm technique / Nur Afzan Mustapha - Mustapha, Nur Afzan (2013)
This paper presents the process of controlling a single phase induction motor speed by using the Pulse Width Modulation (PWM) technique. The PWM pulse will control a single phase full bridge inverter fed to the motor. The pulse was generated digitally in 8bit microcontroller PIC16F877A. The algorithm of producing the PWM pulse with symmetrical regular sampling technique has been shown. The whole system consists of a microcontroller (PIC16F877A) circuit, optoisolator or isolation circuit, IGBT driver and inverter. Choosing IGBT as the switching device gives advantage such as lower switching and conduction losses. The IGBT driver was used to amplify the logic signal from microcontroller so that it has enough voltage to turn on and off the IGBTs. The voltage and the frequency can be changed simultaneously with the pulse width modulation technique.